The Intersection of Turkish and Russian Literature in Georgia: The Effect of Geopolitics on Literature (Global Journal of Human-Social Science, 2023)
Geopolitics refers to a country s position on the mandatory route of the movement areas of high-level values of surrounding countries or regions It has been a determinant for the movement maps of culture and art products and served as the mandatory route of material values before the 21st century Georgia s geopolitics which is at the crossroads linking the north t o the s outh a nd t he E ast t o t he W est h as p layed a determining role in the intersection of culture and art products It has also mediated the acquaintance of different cultures and the production of new art products and compositions by influencing each other This study discussed Georgia s geopolitics decisive role in the intersection of Turkish and Russian literature with one another It was determined by analyzing the literary texts that Georgia s geopolitical location played a pivotal role in intersecting the literature of Turkish and Russian people in biographical narratives and depictions It is possible to see these intersections most clearly in how various literary figures g et a cquainted w ith o ne a nother s styles and recognize the cultural codes asserted by other people s residential representatives and reflect them on their works
Keywords: geopolitics-literature relationship; georgia; turkish literature; russian literature